2007
DOI: 10.1111/j.1365-2842.2006.01676.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep architecture and the apnoea–hypopnoea index in children with obstructive‐sleep apnoea syndrome

Abstract: This study aimed to examine the sleep architecture and craniofacial morphology in a group of children divided by different levels of apnoea-hypopnoea index (AHI), 5, 4.5, 4, 3.5, 3 and 2.5, and to determine an AHI threshold value at which sleep architecture is most affected. 23 children, who were selected from a preliminary questionnaire survey about sleep-related breathing disorders, were evaluated with cephalometric radiographs and overnight polysomnography. The findings indicated that the children with AH1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…We chose to use the AHI as the main measure with the oxygen-desaturation index as a support measure, thus strengthening diagnosis. The reliability of the AHI was confirmed in previous studies, such as Masumoto et al [31], who reported that children with AHI > 3 experienced greater sleep disturbance than those with lower AHI values. Accordingly, AHI ≥ 3 was established as a valid measure for diagnosing sleep patterns, and for differentiating between mild and severe disorders.…”
Section: Discussionsupporting
confidence: 71%
“…We chose to use the AHI as the main measure with the oxygen-desaturation index as a support measure, thus strengthening diagnosis. The reliability of the AHI was confirmed in previous studies, such as Masumoto et al [31], who reported that children with AHI > 3 experienced greater sleep disturbance than those with lower AHI values. Accordingly, AHI ≥ 3 was established as a valid measure for diagnosing sleep patterns, and for differentiating between mild and severe disorders.…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, although there is evidence on serious disturbances in the sleep architecture (SA) of pediatric [9] and adult patients with OSAS [10] and that continuous positive airway pressure therapy provides significant amelioration in SA [11], there is a lack of research aimed at clarifying the relationship between DS, and subjective sleep quality (SSQ) and polysomnography (PSG; SA and sleep-disordered breathing (SDB) features) in patients with PS or OSAS.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumoto et al [15] investigated the characteristics of craniofacial architecture in children with OSAS, and demonstrated that 47% of the children with apnea-hypopnea indexes (AHI) ≥ 3 were considered to have skeletal Class II, and that 63% of the children with AHI < 3 were skeletal Class III. Hoekema et al [16] also indicated that a larger ANB angle was found in children with OSAS.…”
Section: Discussionmentioning
confidence: 99%